Implementation of Powtoon Animation to Enhance Reading Skills of Grade IX C Students - Amalia, Tazkiah; Zainal, Abdul Qahar; Syahrul, Muhammad; Syahid, Akhmad; Abna, Nurjannah (Program Studi Pendidikan Bahasa Arab, Fakultas Agama Islam, Universitas Muslim Indonesia, 2025)
The fundamental premise of this inquiry is directed toward accelerating the competency of maharah al-qirā’ah among students of Class IX C at SMP Islam Al-Bayyinah Makassar, leveraging Powtoon animation media as a pedagogical instrument. The methodological framework adopted embraces a Classroom Action Research (CAR) design oriented toward a mixed-method approach, operationalized through two intervention cycles. Each cycle encompasses critical phases: design, action execution, observation, and reflection. Data collection techniques encompass tests, observations, and interviews. Regarding analysis, qualitative data is processed via reduction, presentation, and conclusion drawing, whereas quantitative data is processed through mean calculation and mastery percentage. Numerical data reveals a significant surge in average scores, escalating from 67.76 in the pre-test to 90.33 by the conclusion of Cycle I, and further advancing from 81.76 to 94.47 in Cycle II. Learning mastery indicators also experienced an escalation, shifting from 41.18% to 88.89% in Cycle I, and from 76.47% to 94.44% in Cycle II. In the qualitative dimension, students exhibited heightened levels of engagement, concentration, and enthusiasm throughout the learning process. This synthesis of data confirms that Powtoon animation media possesses significant efficacy in enhancing students' Arabic text reading capabilities.